Impairments after curative intent treatment for non-small cell lung cancer: A comparison with age and gender-matched healthy controls. Issue 10 (October 2015) - Cavalheri, Vinicius; Jenkins, Sue; Cecins, Nola; Gain, Kevin; Phillips, Martin; Sanders, Lucas H.; Hill, Kylie
Abstract: Background: The aim of this study was to compare measures of exercise capacity, health-related quality of life (HRQoL), muscle force, lung function and feelings of anxiety and depression in people after curative intent treatment for NSCLC with age and gender-matched healthy controls. Methods: This cross-sectional study included 23 participants (68 ± 10yr; 16 females), 6–10 weeks after lobectomy for NSCLC or, for those who received adjuvant chemotherapy, 4–8 weeks after their last cycle. The study also included 20 age and gender-matched healthy controls (69 ± 5yr; 13 females). All participants underwent measurements of exercise capacity (cycle-ergometry test [CPET] and 6-min walk test [6MWT]), HRQoL (Short-Form 36 general health survey [SF-36]), handgrip force, quadriceps torque, lung function and feelings of anxiety and depression. Results: When compared with data collected in healthy controls, those in the NSCLC group demonstrated impairments in the peak rate of oxygen consumption (15 ± 3 versus 24 ± 7 ml kg −1 ·min −1 ; p < 0.001) and maximum work rate (75 ± 25 versus 127 ± 51Watts; p < 0.001) measured during the CPET, and 6-min walk distance (494 ± 77 versus 649 ± 61 m; p < 0.001). Similarly, impairments were demonstrated in all domains of the SF-36 ( p < 0.01 for all), isometric handgrip force (28 ± 7 versus 34 ± 10 kg; p = 0.02), and all measures of lung function ( p ≤ 0.001 for all). A higher score for depression was also seen (3.0 ± 2.5 versus 1.5 ± 1.6; p = 0.03). There was no difference between the groups in isometric quadriceps torque or feelings of anxiety. Conclusions: After curative intent treatment for NSCLC, compared to healthy controls, impairments were demonstrated in laboratory and field-based measures of exercise capacity, HRQoL, isometric handgrip force and lung function. Although people after curative intent treatment for NSCLC reported greater feelings of depression, these levels were below those considered clinically relevant. These findings suggest that people after curative intent treatment for NSCLC may benefit from rehabilitative strategies to optimise exercise capacity and HRQoL. Highlights: Use of stratified sampling to select healthy controls. Use of both laboratory- and field-based exercise test to assess exercise capacity. Seventy-one per cent of patients presented impairments in maximal exercise capacity. Patients also had impairments in quality of life, handgrip force and lung function.